Designing Project-Based Learning Syllabus for Speaking for Informal Interaction Course Integrating Local Coastal Culture - Hanifah Hanifah; Candra Muhammad; Nainggolan Elsa Ernawati; Firmansyah Bianca Naluri; Sartika Delita; Hasyim Taufiqurrahman (SHS Web of Conferences)
Syllabus is a dynamic document that outlines the learning outcome, material, method, and assessment conforming to the students’ needs. Due to the absence of the reforming syllabus of the Speaking for Informal Interaction (SII) course at English study program Universitas Maritim Raja Ali Haji, this study purposes to create a project-based learning syllabus for the course. To achieve the objectives, the defining and designing stages of Thiagarajan et al.'s four-D model were employed. Two research instruments were used to gather the data: interview guideline and questionnaires. Three assistant professors and 35 students took part in this study. In addition, curriculum analysis was done to create the syllabus's structure. Considering the data gathered, the syllabus was created by incorporating local coastal culture into its contents and activities or projects. The indicators chosen based on the curriculum analysis show that the students meet the expected graduate profile if they can communicate effectively connected to actual situations. The SII syllabus prototype will be used further in the development and dissemination phase for real-world implementation.